147k views
4 votes
Please help me figure out this problem

Please help me figure out this problem-example-1

1 Answer

6 votes

Answer:


f(g(x))=f\left(-(3x+21)/(5)\right)=x\\\\g(f(x))=g\left(-(5)/(3)x-7\right)=x

Explanation:

Fill in the given expressions and simplify.


f(g(x))=f\left(-(3x+21)/(5)\right)=-(5)/(3)\left(-(3x+21)/(5)\right)-7\\\\=\left(-(5)/(3)\right)\left(-(3x)/(5)\right)-\left((5)/(3)\right)\left(-(21)/(5)\right)-7\\\\=(15x)/(15)+(5\cdot 21)/(3\cdot 5)-7=x+7-7=x

Going the other way, we have ...


g(f(x))=\displaystyle -(3\left(-(5)/(3)x-7\right)+21)/(5)=-(-5x-21+21)/(5)=x

User Joshdick
by
5.9k points